2016
DOI: 10.1186/s12940-016-0147-7
|View full text |Cite
|
Sign up to set email alerts
|

Toddler temperament and prenatal exposure to lead and maternal depression

Abstract: BackgroundTemperament is a psychological construct that reflects both personality and an infant’s reaction to social stimuli. It can be assessed early in life and is stable over time Temperament predicts many later life behaviors and illnesses, including impulsivity, emotional regulation and obesity. Early life exposure to neurotoxicants often results in developmental deficits in attention, social function, and IQ, but environmental predictors of infant temperament are largely unknown. We propose that prenatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 83 publications
0
25
0
Order By: Relevance
“…The LCA can be used as a single neurodevelopmental outcome in multinomial logistic regression modelling to reveal associations between NICU-based exposures and the latent class. As in our prior work,75 LCA can also facilitate probabilistic modelling of the association between a neurophenotype and concurrent NICU-based exposure to varying levels of multiple exposures.…”
Section: Cohort Descriptionmentioning
confidence: 93%
“…The LCA can be used as a single neurodevelopmental outcome in multinomial logistic regression modelling to reveal associations between NICU-based exposures and the latent class. As in our prior work,75 LCA can also facilitate probabilistic modelling of the association between a neurophenotype and concurrent NICU-based exposure to varying levels of multiple exposures.…”
Section: Cohort Descriptionmentioning
confidence: 93%
“…Pregnancy and neonatal complications such as hypertension, preeclampsia, and gestational diabetes [ 8 ]; low birth weight, foetal growth restriction [ 9 , 10 ] and preterm birth [ 11 13 ] are more likely in individuals who experience antenatal depression and anxiety. Depression and anxiety during pregnancy have also been associated with poor cognitive, emotional and behavioural development of the infant [ 12 , 14 16 ], poor maternal attachment to the infant and increased risk of depression in partners [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yet there is concern that chemicals commonly found in children’s environments may adversely influence social and emotional behavioral development [11]. For instance, epidemiological studies have reported that children with higher lead exposure have a greater probability of demonstrating negative social behaviors in toddlers, children, and young teens [1214]. Exposure to bisphenol A (BPA), an endocrine disrupting chemical, has also been linked to behavioral outcomes in young children [15, 16].…”
Section: Introductionmentioning
confidence: 99%